2017
DOI: 10.1007/s41782-017-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Poor Knowledge and Attitude Regarding Obstructive Sleep Apnea (OSA) Among Medical Students in India: A Call for MBBS Curriculum Change

Abstract: Context and AimsSleep disorders are one of the most common disorders but are not given enough importance in medical teaching. This study was done to find the knowledge of medical students about the most common sleep disorders. Design Cross-sectional study. Methods and Materials A total of 232 final-year medical students from four medical colleges filled up OSAKA and OSAKAkids questionnaire. Statistical Analysis Used Demographic variables were summarized by descriptive statistic measures like counts and percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
(14 reference statements)
1
20
0
Order By: Relevance
“…Finally, students are evaluated on five spotters from the undergraduate (UG) curriculum of psychiatry to have a well-rounded assessment. They are expected to analyze the given clinical information in association with one of the following – (i) EEG; (ii) computed tomography (CT), or MRI scan of the brain, which is part of UG curriculum internationally;[ 29 ] (iii) functional neuroimaging – single-photon emission CT of the brain – specially to identify areas of hypometabolism in common conditions such as dementia and depression;[ 30 ] (iv) findings on polysomnography (hyponograms, epochs showing respiratory apneas) as sleep disorders are common and have huge health and economic impact;[ 31 ] (v) photographs of stigmata (loss of hair in trichotillomania, ash leaf spots, and Shagreen patches of tuberous sclerosis); (vi) videos of clinical findings (tics or disorientation); (vii) instruments used in neuromodulation, sleep disorders, and substance use disorders; (viii) drugs used in psychiatry practice; and (ix) laboratory reports. The multidimensional assessment helped students to balance weak domain against strengths.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Finally, students are evaluated on five spotters from the undergraduate (UG) curriculum of psychiatry to have a well-rounded assessment. They are expected to analyze the given clinical information in association with one of the following – (i) EEG; (ii) computed tomography (CT), or MRI scan of the brain, which is part of UG curriculum internationally;[ 29 ] (iii) functional neuroimaging – single-photon emission CT of the brain – specially to identify areas of hypometabolism in common conditions such as dementia and depression;[ 30 ] (iv) findings on polysomnography (hyponograms, epochs showing respiratory apneas) as sleep disorders are common and have huge health and economic impact;[ 31 ] (v) photographs of stigmata (loss of hair in trichotillomania, ash leaf spots, and Shagreen patches of tuberous sclerosis); (vi) videos of clinical findings (tics or disorientation); (vii) instruments used in neuromodulation, sleep disorders, and substance use disorders; (viii) drugs used in psychiatry practice; and (ix) laboratory reports. The multidimensional assessment helped students to balance weak domain against strengths.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Total knowledge score was 37.9% and 42.1% for OSAKA and OSAKA-KIDS, respectively. They found that there was not enough knowledge in spite of enough attitude and thinking about the importance of the disorder19 . Jokubauskas et al (2018) in a nation-wide study in Lithuania, studied knowledge and attitude of 353 dentists using OSAKA.…”
mentioning
confidence: 99%
“…This issue of the journal contains an article that discussed the dismal state of education regarding sleep disorders in medical curriculum [1]. Authors report that despite having some information regarding the clinical presentation of obstructive sleep apnea (OSA), students were not able to deduce its clinical importance [1].…”
mentioning
confidence: 99%
“…Authors report that despite having some information regarding the clinical presentation of obstructive sleep apnea (OSA), students were not able to deduce its clinical importance [1]. This information is important in light of the evidence that shows that obesity is a global epidemic, increasing especially among minority population in the USA and in developing countries [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation